DIALOGUE AND THEOLOGY OF RELIGIOUS PLURALISM: THEOLOGICAL REFLECTIONS - Vineeth, V F (Journal of Dharma, 1989)
Man is dialogical by nature. Characterized by self-awareness he communicates himself to others through dialogue. Thus dialogue is not something novel to the human race. It is an essential part of human nature. However the word dialogue has assumed new dimensions of meaning in recent days. This is especially so when the word is used in relation with the world-religions or world-visions which in the contemporary world very often work as quasi-religions. l We are now living in a world of dialogue between religions and world-visions. Some sort of a dialogue was going on between religions from time immemorial. Any encounter of one religion with another religion calls for some kind of a dialogue. But this need not be a dialogue that brings about any transformation in the partners. A real dialogue presupposes an attitude which is open to the other person, respectful towards him and even a readiness to be changed by the graceful touch of his presence. This is what is new to the word dialogue today, when it is applied in the context of religions. Human communication is no more in the style of an unilateral monologue as it was in the time of imperialistic monarchies and the colonialist expansion of the West to the East. Mankind has developed its own consciousness that it now understands the anomaly of the dictatorial approach to the factors of life.